Instrument about knowledge, attitudes, and practices of pregnant women about the hypertensive disease of pregnancy - Lia Maristela da Silva Jacob; Maria Helena Baena de Moraes Lopes; Antonieta Keiko Kakuda Shimo (Universidade Federal do Ceará, 2021)
Objective: to elaborate and validate an instrument to evaluate the knowledge, attitudes, and practices of pregnant women regarding the hypertensive disease of pregnancy. Methods: methodological research, to develop and validate an instrument about the knowledge, attitudes, and practices of pregnant women regarding said disease. The stages of the design were: elaboration, content validation, and semantic analysis with the target audience. Results: to elaborate the instrument, the following items were adopted: definition, classification, signs and symptoms, risk factors, consequences, prevention and treatment of the hypertensive disease of pregnancy. The instrument was submitted to a validation by specialists. Its dimensions presented a Content Validity Index of 0.85, 0.89 for pertinence, 0.81 for clarity, and 0.86 for scope. The variable attitudes was below 0.8 in all dimensions. Conclusion: the instrument was considered to be valid and can be used to direct educational interventions, aimed to prevent the disease or its complications from surfacing.